Damage and people Covers Portfolio between excess and Negligence - A Deep Radical Shifts - - Guendouz, Tarek; Belhimer, Brahim; Gasmi, Said (Dirassat Journal Economic Issue, 2020)
The aim of this article is to diagnose product portfolio of The Algerian insurance market during the period of 1995-2012, which is considered as an evaluative process for the outcome of liberal reforms initiated by the government authorities, through the enactment of Law No. 04.06 , dated at 20-04-2006 amending and supplementing Law No. 95 / 07 dated at 01.25.1995, which aims to improve the Underwriting performance of insurance companies active in Algeria, the adoption of separation of life insurance from damages insurance was the most important decisions taken in this frame, which became effective from the beginning of March 2011, it has led to a change of the rules of the competitive game between the suppliers, and the objective of authorities commandment was the advancement of all branches (auto insurance, Life insurance, the agricultural; industrial’s damages insurance, transportation insurance, the loan insurance, etc ...).